Menggali Makna Doa Wudhu dalam Perspektif Medis - Hanifa, Annahdiya Rafiul; Pradana, Falih Satria; Praja, Shafa Ananti (Maliki Interdisciplinary Journal, 2025)
Ablution (wudu) is one of the requirements for valid prayer, possessing not only spiritual significance but also health benefits. This paper aims to examine the meaning of ablution prayers from a medical perspective and explain the relationship between ritual worship and physical and mental health. Through a literature review, it was found that the practice of ablution offers medical benefits, including preventing the transmission of disease through the cleanliness of the washed body parts, maintaining oral and skin health, and promoting nervous relaxation. Furthermore, the prayers recited during ablution serve as positive suggestions that play a role in reducing stress, increasing mental peace, and strengthening psychological balance. The integration of ablution and prayer demonstrates the holistic concept of health in Islam, which unites the physical, spiritual, and spiritual dimensions. Thus, this study confirms that Islamic teachings are not only of worship value but also align with the principles of modern medicine in maintaining the quality of human life.